Evaluating the Reading Competencies of New Employees in Islamic Commercial Organizations with the Focus on the Islamic Banking Sector - Ashiq Hussain (Pakistan Journal of Islamic Research)
Islamic Banking has emerged as a new phenomenon in the present world. Islamic banks recruit graduates who have been recipients of degrees related commerce education: B.Com, M.Com, MBA Banking and Finance etc. Commerce education in Pakistan is significant as it ensures good jobs for the graduates in the field. However, stakeholders believe that the commerce graduates' competence in English language skills is not up to the mark which poses serious threats in their professional situations. Within the field of commerce, the study is narrowed down to the Islamic banking sector’s new employees’ reading comprehension performances. In the context of occupational reading abilities of the newly recruited fresh graduates, Islamic bank managers’ perceptions have been recorded. Interview was chosen as a tool for this case study. Data has been analyzed qualitatively. The findings reveal that serious communication failures occur very frequently that cause unnecessary delays at work places with reference to professional tasks. To address the problem, certain recommendations are given in the end of this research.